ANALYSIS OF TOURIST ATTRACTION ON TOURIST INTEREST IN VISITING KERANGGAN TOURISM VILLAGE SOUTH TANGGERANG - Vannessa Lie; Dewanta Facrureza (ZILLZELL MEDIA PRIMA, 2024)
This research is motivated by the development of tourist destinations today so as to increase competitiveness between tourist destinations. Tourism Attraction is the most important factor and the main driver in tourism activities, because tourist attraction is a determining factor to make tourists have an interest in visiting a tourist destination. This study intends to see the influence of tourist attraction on interest in visiting Keranggan Tourism Village. This study used a causal analysis method with a quantitative approach. Data collection techniques by observation, interviews and questionnaires. The sample in this study was tourists who had visited 100 people based on the non-probability method with purposive sampling techniques. The analytical techniques used in this study are validity tests, reliability tests, classical assumption tests, simple linear regression, description (average) t tests, and R2 analysis. The results of this study explain that: 1). Tourism Attraction 4A has a significant effect on Interest in Visiting Keranggan Tourism Village Destinations.